2003
DOI: 10.1152/japplphysiol.00291.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of l-glutamate in systemic AVP-induced hypothermia

Abstract: It has been reported that systemic injection of arginine vasopressin (AVP) induces a drop in body core temperature (T(c)), but little is known about the mechanisms involved. Because glutamate is an important excitatory neurotransmitter involved in a number of thermoregulatory actions, in the present study, we tested the hypothesis that glutamate plays a role in systemic AVP-induced hypothermia. Wistar rats were pretreated intracerebroventricularly (icv) with kynurenic acid, an antagonist of l-glutamate ionotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Recently, VP has been invoked as one of the main endogenous antipyretic molecules (5,34,39,46), and evidence has been presented that VP plays a tonic role in thermoregulation, although it is uncertain which receptors are involved (46). Our data support a role for VP in thermoregulation under basal conditions, as blockade of V 1a receptors significantly increased T b in freely moving rats.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, VP has been invoked as one of the main endogenous antipyretic molecules (5,34,39,46), and evidence has been presented that VP plays a tonic role in thermoregulation, although it is uncertain which receptors are involved (46). Our data support a role for VP in thermoregulation under basal conditions, as blockade of V 1a receptors significantly increased T b in freely moving rats.…”
Section: Discussionsupporting
confidence: 71%
“…Vibrational transitions of various 1 O 2 pairs lead to UPE emission with spectral peaks at approximately 470-480, 510-530, 560-580, 630-640, and 670 nm (Nakano et al, 1976). Another peak is at 703 nm (Khan and Kasha, 1970) and approximately 1270 nm (Baker and Kanofsky, 1991 In addition, as mentioned, glutamate has a significant function in thermoregulation by means of the NMDA ionotropic receptors (Yoshimatsu et al, 1993;Paro et al, 2003), and there is a significant association between temperature and glutamate excitotoxicity (Campos et al, 2012). Thus, glutamate-related phosphene induction through UPE may also be a possible mechanism relating fever (high body temperature) and phosphenes (Cervetto et al, 2007).…”
Section: Glutamate Triggered Upe and Phosphenesmentioning
confidence: 95%
“…the principal excitatory neurotransmitter in the central nervous system) is distributed widely throughout the neuroaxis. L-glutamate has a significant role in thermoregulation through NMDA ionotropic receptors (Yoshimatsu et al, 1993;Paro et al, 2003). There is a tight association between temperature and glutamate excitotoxicity (Campos et al, 2012).…”
Section: Phosphenes Due To Excess Upe Caused By Increased Ros Productmentioning
confidence: 99%
“…AVP has also been reported to work as an endogenous antipyretic molecule in the CNS (243,263,368). The AVP-induced reduction in body temperature is caused partly by a reduction in the metabolic rate associated with the suppression of the lipid metabolism (243,395). Since such changes also occurred in AH-lesion rats, it has been concluded that AVP injected peripherally does not act on the hypothalamic thermoregulatory center but on the peripheral metabolic tissues (243,395).…”
Section: Water Homeostasis and Thermoregulationmentioning
confidence: 99%